Effect of Biochar Addition on the Microbial Community and Methane Production in the Rapid Degradation Process of Corn Straw - Zhi Wang; Ying Guo; Weiwei Wang; Liumeng Chen; Yongming Sun; Tao Xing; Xiaoying Kong (Energies, 2021)
Anaerobic digestion with corn straw faces the problems of difficult degradation, long fermentation time and acid accumulation in the high concentration of feedstocks. In order to speed up the process of methane production, corn straw treated with sodium hydroxide was used in thermophilic (50 °C) anaerobic digestion, and the effects of biochar addition on the performance of methane production and the microbial community were analyzed. The results showed that the cumulative methane production of all treatment groups reached over 75% of the theoretical methane yield in 7 days and the addition of 4% biochar increased the cumulative methane production by 6.75% compared to the control group. The addition of biochar also decreased the number of biogas and methane production peaks from 2 to 1, and had a positive effect on shortening the digestion start-up period and reducing the fluctuation of biogas production during the digestion process. The addition of 4% biochar increased the abundance of the bacterial family Peptococcaceae throughout the digestion period, promoting the hydrolysis rate of corn straw. The dominant archaeal genus Methanosarcina was significantly more abundant at the peak stage and the end of methane production with 4% biochar added compared to the control group.